Implementation of the Rebo Nyunda Program at SDIT Al-Taftazani in Pedagogical Studies - Wulandari, Dinda Ayu; Triatna, Cepi; Nuryani, Pupun (International Conference on Elementary Education, 2022)
This research is motivated by the lack of attention to educational practices on program policies carried out in schools. The Rebo Nyunda program is a policy of the Bandung City and Regency Government that aims to preserve Sundanese culture. This study aims to describe pedagogical studies, especially educational goals, the role of educators, and the role of students in the implementation of the Rebo Nyunda program at SDIT Al-Taftazani. This research is qualitative research using descriptive research methods. The results showed that: (1) the educational objectives in the Rebo Nyunda program need to be aligned with the national education goals; (2) the role of educators in the Rebo Nyunda program is only as a guide and as an example for the children, so it needs to be adjusted to the characteristics of an educator; (3) the role of students in the Rebo Nyunda program is not only seen as subjects but as individuals who can develop and have potential. The results of this study can be used to understand how pedagogical studies are carried out in the Rebo Nyunda program.